Exergy, Energy, and Dynamic Parameter Analysis of Indigenously Developed Low-Concentration Photovoltaic System - Pankaj Yadav; Brijesh Tripathi; Manoj Kumar (International Journal of Photoenergy)
Piecewise linear parabolic trough collector (PLPTC) is designed and developed to concentrate solar radiation on monocrystalline silicon based photovoltaic module. A theoretical model is used to perform electrical energy and exergy analysis of low-concentration photovoltaic (LCPV) system working under actual test conditions (ATC). The exergy efficiency of LCPV system is in the range from 5.1% to 4.82% with increasing rate of input exergy rate from 30.81 W to 96.12 W, when concentration ratio changes from 1.85 to 5.17 Sun. Short-circuit current shows increasing trend with increasing input exergy rate of ≈0.011 A/W. Power conversion efficiency decreases from 7.07 to 5.66%, and open-circuit voltage decreases from 9.86 to 8.24 V with temperature coefficient of voltage ≈-0.021 V/K under ATC. The results confirm that the commercially available silicon solar PV module performs satisfactorily under low concentration.